Performance and emissions of diesel engine fuelled with preheated biodiesel fuel derived from crude palm, jatropha, and waste cooking oils - Khalid, Amir; Manshoor, Bukhari; Mohmad Jaat, M. Norrizam; Tajuddin, A. S. A.; Syahrunniza, Hadi; Nursal, Ridwan Saputra; Zaman, I. (UMP Publisher, 2017)
Biodiesel is typically made by chemically reacting lipids of palm, vegetable, and waste cooking oils and animal fat with an alcohol producing fatty acid esters. Biodiesel is not efficient in cold weather and this is biodiesel’s major problem. Viscosity has influences on the fuel flow rate and leads to poor fuel atomisation during the combustion process. The aim of this study is to determine the effects of biodiesel temperature in the range fom 40 °C and 60 °C on engine performance such as torque, brake power, brake mean effective pressure, and fuel consumption. Three types of biodiesel oil were used (crude palm oil (CPO), waste cooking oil (WCO), and jatropha oil) under biodiesel blending ratio of 5vol%. A single cylinder four-stroke engine was used and operated under different load conditions of 0% and 50% and observed emission of CO, CO2, NOx, and HC. The engine operated at 0% and 50% dynamometer load conditions and running speeds of the engine of 800 rpm, 1200 rpm, 1600 rpm, and 2000 rpm. The results of this study showed that the heating temperatures in the range from 40 °C and 60 oC in CPO10 produced the highest brake power as well as torque and BMEP. For the experimental results of exhaust emission, the preheated temperature affected the degradation of the exhaust emission. In addition, preheated biodiesel increased the pressure on the cylinder combustion chamber. It can be concluded that the biodiesel preheated blend influences the performance and emission. For CPO biodiesel, the preheated biodiesel decreased CO and NOx while the standard diesel produced the lower emission of CO2 and HC. WCO biodiesel blend produced a lower emission with increasing fuel temperature.